Research on reverse osmosis membrane fouling during the treatment of chemical wastewater by double membrane method - QI Yingying; SU Yangzhou; CHENG Xiaoying; LIU Qiang; ZHANG Xiaolei (Gongye shui chuli)
The double-membrane combination process based on reverse osmosis (RO) membrane is widely used in wastewater reuse treatment. The treatment efficiency of different RO combination processes (UF-RO,UF-NF-RO,UF-RO-RO) on the main pollutants of chemical wastewater was studied. The morphology and characteristics of the membrane pollution layer were revealed by analyzing the membrane flux in the process of chemical wastewater treatment by different RO combination processes, the amount, content and composition of fluorescent organic matter in the effluent, organic and inorganic pollutants on the membrane surface. The results showed that UF-RO and UF-NF pretreatment could slow down the decline of RO membrane flux, but the membrane flux was still serious after 8 hours. The COD, TP, and TN of effluent were all low, and the TN removal rate was greater than 95%, when the chemical water was treated by double membrane methods. Fluorescent organic matter was significantly reduced in the effluent after UF-RO, UF-NF-RO and UF-RO-RO treatment, mainly due to RO interception of organic matter from wastewater. The pollutants on the surface of the RO membrane mainly included inorganic pollutants (such as calcium and magnesium) and protein-based organic pollutants, and there was a certain amount of accumulation on the subsequent RO surface, which proved that there were still pollutants after UF, NF, RO and other pretreatments, leading to serious membrane fouling problems.